2012
DOI: 10.1002/anie.201205475
|View full text |Cite
|
Sign up to set email alerts
|

Azo‐Propofols: Photochromic Potentiators of GABAA Receptors

Abstract: Shine and rise! GABAA–receptors are ligand-gated chloride channels that respond to the major inhibitory neurotransmitter of the mammalian central nervous system. Herein, we introduce azobenzene derivatives of propofol that increase GABA-induced currents when irradiated with light and thus function as photochromic potentiators. One of our molecules, AP2, can be employed as a light-dependent general anesthetic in translucent tadpoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
89
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(91 citation statements)
references
References 25 publications
0
89
0
2
Order By: Relevance
“…35 We also found that tetra-ortho-thioether groups (21) could be used to circumvent reduction while enhancing the molar absorption coefficient in the red region compared to the tetra-ortho-chloro species. 36 About the same time, Hecht's group synthesized the tetra-ortho-fluoro substituted species (22). 60 While this does not have the same degree of n−π* red shifting, it has an extraordinarily slow thermal cis-to-trans relaxation rate (years) so that it is truly bistable on biological time scales.…”
Section: ■ Tetra-ortho-methoxy Substitutionmentioning
confidence: 98%
“…35 We also found that tetra-ortho-thioether groups (21) could be used to circumvent reduction while enhancing the molar absorption coefficient in the red region compared to the tetra-ortho-chloro species. 36 About the same time, Hecht's group synthesized the tetra-ortho-fluoro substituted species (22). 60 While this does not have the same degree of n−π* red shifting, it has an extraordinarily slow thermal cis-to-trans relaxation rate (years) so that it is truly bistable on biological time scales.…”
Section: ■ Tetra-ortho-methoxy Substitutionmentioning
confidence: 98%
“…Extension of propofol to the azobenzene AP-2 provided a photoswitch for the optical control of inhibitory GABA currents. 34 Amiloride and its more lipophilic congener phenamil are clinically used blockers of epithelial sodium channels (ENaC). Our photoswitchable version, PA-1, could be used to optically control the δβγ-isoform of these important channels.…”
Section: Accounts Of Chemical Researchmentioning
confidence: 99%
“…They are important for signaling and neuronal function. There has been much progress in the field of light-controlled neuronal signaling, and these advances have extended to living cells and organisms [1,8,73,74]. The combination of synthetic photoswitches and naturally occurring receptor proteins has proved to be an effective means for rapidly and reversibly controlling channel function, and have aided in studying processes related to channel function.…”
Section: Photoswitchable Ion Channels and Receptorsmentioning
confidence: 99%
“…This approach involves genetic manipulation of the protein so that a reactive cysteine residue can be placed in a specific site on the receptor. A second method involves a small molecule ligand that contains a head group that resembles a known receptor agonist or antagonist [74,[79][80][81][82][83][84][85]. The affinity is light dependent, the conformation of one isomer interferes with binding and/or activation and the other permits it.…”
Section: Photoswitchable Ion Channels and Receptorsmentioning
confidence: 99%